Step by Step® Hospital Designing and Planning - Malhotra Jaideep, Malhotra Narendra; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2010)
This unique book on Hospital Designing and Planning is being presented to you under Dr Malhotra s Series of books. Most of us are professional doctors who are usually too busy to pay attention to subtle planning of our clinics, nursing homes and hospitals. In this book presented stepwise approach to designing and building a clinic or a hospital.
Keywords: Hospital Administration; Electronic books